Literature Review on Chemical Compounds from Natural Ingredients that Function as Anti-Hypertension - Nur, Andi Bulqiah (Hayyan Journal, 2025)
Hypertension is one of the most common health problems worldwide and is a major risk factor for cardiovascular diseases such as coronary heart disease and stroke. Many synthetic drugs are available to manage hypertension, but they often have significant side effects. Research on chemical compounds from natural materials that have antihypertensive activity is very important. This literature review aims to evaluate various chemical compounds that are derived from natural materials and have potential as antihypertensive agents. Some of the plants that have been identified as having active chemical compounds include Hibiscus sabdariffa which contains anthocyanins, Allium sativum (garlic) which contains allicin, and Andrographis paniculata which contains andrographin. Recent studies have shown that these compounds are effective in lowering blood pressure through various mechanisms such as vasodilation, diuresis, and inhibition of angiotensin-converting enzyme (ACE). This study highlights the importance of using natural ingredients as a safer and more effective alternative to synthetic drugs for the management of hypertension. However, more research is needed to develop more effective drug formulations and to test their effectiveness clinically in human populations.